The Effect of E-Service Quality and Price on Customer Satisfaction and Loyalty of Traveloka in Pekanbaru - Firdaus Josua; Alvi Furwanti Alwie; Susi Hendriani (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2017)
Marketing activities of online services are often seen on the achievement of strategies for achieving customer loyalty through customer satisfaction. Taking heed of e-service quality and price constitutes an appropriate marketing strategies to foster the users of online services’ satisfaction. Providing service and good benefits with a relatively cheap price to meet the expectations and needs of the customers will affect the level of satisfaction of online services users. The consumer satisfaction maintained by online service providers will create loyal customers. The purpose of this study to test how much the e-service quality and prices influences directly to customer satisfaction and loyalty. In addition, this study examine the relationship of satisfaction and customer loyalty. This research was conducted in Pekanbaru to 200 sample respondents from the users of online flight tickets searching service, Traveloka, from September to October, 2016.Data collection techniques used is a questionnaire with Likert scale using non-probability sampling method. Data were analyzed using SEM analysis techniques, which are used as the instrument in testing hypothesis by using AMOS 21 program.The results of this study indicated that the overall dimensions of e-service quality have positive and significant impact on customer satisfaction and loyalty. Price is another factor that gives positive and significant impact directly on the customer satisfaction as well as loyalty. Consumer satisfaction can be a moderator variable between e-service quality and price to customer loyalty.